Review and analysis of advances in functionalized, smart, and multifunctional asphalt mixtures. (November 2021) - Segundo, I. Rocha; Freitas, E.; Branco, V.T.F. Castelo; Landi, S.; Costa, M.F.; Carneiro, J.O.
Abstract: Road pavements are designed to withstand road traffic and weathering actions while ensuring comfortable and safe riding conditions as well as low costs and damage to the environment. When a road pavement has additional abilities or reacts to an external stimulus, it is considered to be smart and multifunctional. Examples of such abilities that have been investigated in asphalt mixtures are photocatalytic, superhydrophobic, self-cleaning, de-icing/anti-icing, self-healing, thermochromic, and latent heat thermal energy storage abilities. These abilities are developed using different materials such as nano/microparticles (including semiconductor materials and microcapsules), fibers, phase change materials (PCMs), and dyes, often using dissimilar techniques such as spray coating, volume incorporation, spreading, and asphalt binder modification. Owing to their large surface areas, road pavements are true recipients for large amounts of nano/micromaterials, and consequently, act as important "tools" to stimulate an emerging sector related to the scale of production of materials in the form of nanoparticles. Moreover, smart and multifunctional road pavements can be included in the domain of clean technology (e.g., photocatalytic pavements that promote the environmental depollution of NOx -type gases emitted as vehicle exhaust gases). In this context, they can contribute to materializing the transition to a novel socio-economic model known as "Green Recovery" that is environmentally friendly, sustainable, and inclusive. This model is a very important path toward economic and employment recovery, a vision to which many countries are strongly committed. Therefore, this work reviews new capabilities imparted to asphalt mixtures and provides recommendations. Highlights: Roads supply socioenvironmental benefits by smart and multifunctional capabilities Application of nanomaterials does not require expensive technological improvements Photocatalytic, thermochromic, and LHTS provide socio and/or environmental benefits Superhydrophobic, LHTS, self-healing, and thermochromic improves mechanical behavior Superhydrophobic, self-cleaning, and de-icing capabilities are related to safety.